2003
DOI: 10.1098/rspb.2003.2416
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, hypermutation, within–host evolution and the virulence ofNeisseria meningitidis

Abstract: Many so-called pathogenic bacteria such as Neisseria meningitidis, Haemophilus influenzae, Staphylococcus aureus and Streptococcus pneumoniae are far more likely to colonize and maintain populations in healthy individuals asymptomatically than to cause disease. Disease is a dead-end for these bacteria: virulence shortens the window of time during which transmission to new hosts can occur and the subpopulations of bacteria actually responsible for disease, like those in the blood or cerebral spinal fluid, are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 32 publications
2
45
0
1
Order By: Relevance
“…In an in vivo infant rat model of bacteraemia, they showed that the hypermutable variant could escape the bactericidal activity of the serum and was more virulent than strain 8047, avoiding the passive protection of mAb B5. Mathematical epidemiology models and within-host infection dynamics previously predicted this result (Meyers et al, 2003).…”
Section: Possible Links To Virulencementioning
confidence: 97%
“…In an in vivo infant rat model of bacteraemia, they showed that the hypermutable variant could escape the bactericidal activity of the serum and was more virulent than strain 8047, avoiding the passive protection of mAb B5. Mathematical epidemiology models and within-host infection dynamics previously predicted this result (Meyers et al, 2003).…”
Section: Possible Links To Virulencementioning
confidence: 97%
“…The second strain, which we will refer to as invasive, causes as many new infections as the benign strain but, upon acquisition, occasionally causes meningococcal disease. This distinction between a completely benign and an invasive strain is motivated by the observation that the diseasecausing potential of N. meningitidis on average is very low, in the order of 0.0001 (13). The pathogenicity of certain lineages, although still small in absolute terms, appears to be at least an order of magnitude higher than this.…”
Section: A Model For Meningococcal Diseasementioning
confidence: 99%
“…Although strains can appear through introduction from another locality, mutation, or recombination, a mechanism that could lead to the repeated appearance of invasive strains with a relatively high rate is the switching on of contingency genes through phase shifting (13,19,20). We, therefore, added a transition to our model that lets a very small fraction, Ͻ Ͻ , of infections with the benign strain result in carriage of the invasive strain and, to keep the population size constant, adjusted the force of infection of the benign strain to ␤(1 Ϫ )(I͞N).…”
Section: A Model For Meningococcal Diseasementioning
confidence: 99%
“…These models suggest that the optimal level of virulence is just below that sufficient to kill the host. However, many pathogens appear to be maintained at levels far below those necessary to induce host mortality (Levin & Antia 2001;Meyers et al 2003), with death only occurring in immuno-compromised hosts. Hence, there may be some other limitation to high virulence that is reached before host mortality occurs and it may be that over-stimulation of the host's immune response can act as a sufficient constraint to restrict the evolution of high levels of pathogen virulence.…”
Section: The Evolution Of Pathogen Virulencementioning
confidence: 99%